Departing in Style Columbia Bar and River Pilots often come aboard and disembark via helo due to the legendarily rough seas of the Columbia Bar. I like to think they were just showing off for us on this day. The Washington/Oregon border can be seen on the horizon. - Snyder, Jake
TSGB Cruise 2013"